SINDIKASI JUAL-BELI KUNCI JAWABAN UJIAN NASIONAL 2010 (STUDI KASUS JARINGAN JUAL-BELI KUNCI JAWABAN UJIAN NASIONAL 2010 DI KOTA X) - Ika Novitasari (Jurnal Kriminologi Indonesia, 2011)
This research focuses on the existence of the siyndicate that allegedly buys the answer key of the 2010 National Test in X city. There is a lot of people that getting involved in this answer key trading; the printing clerk works at the printing service where the test was printed, Education Service staff, the teacher at the certain school where this trading occured, KBB gang who trading this answer key in fifteen High Schools at X city, and the student who bought the answer key. This research uses such qualitative method with descriptive design and using observational approach to collect the data or information. This research found that there is a sophisticated network, towards to syndicate, in this illegal trading crime, with a temporal behaviour which formed by collective and mutual benefits between them.